Cellular mechanisms involved in the pathogenesis of airway remodeling in chronic lung disease. Issue 1 (31st December 2022) - Arellano-Orden, E.; Calero Acuña, C.; Sánchez-López, V.; López Ramírez, C.; Otero-Candelera, R.; Marín-Hinojosa, C.; López Campos, Jl
ABSTRACT: Background: Airway epithelial cells and lung fibroblasts play an important role in the development of chronic lung disease, but the exact mechanisms responsible have not been clarified. Our objective was to investigate the involvement of these cells in the inflammatory response associated to chronic lung disease. Methods: Human lung fibroblasts and airway epithelial cells were challenged with Interleukin-1β and hypoxia, and with inhibitory (simvastatin) stimuli of the inflammatory response. Expression of markers of local inflammation ((IL-8, monocyte chemoattractant protein-1 (MCP-1), factor-κB1 (NF-κB1)), systemic inflammation ((C-reactive protein (CRP) and serum amyloid A (SAA)) and proteases matrix metalloproteinase (MMP) 9 and 12 were assessed by PCR and ELISA. Apoptosis/necrosis was analyzed by flow cytometry. Results: Our results showed that the lung fibroblasts had a higher expression of local and systemic inflammation and protease activity markers when they were treated with IL-1β compared to airway epithelial cells. Under hypoxic conditions, we observed a decrease in systemic inflammation in lung fibroblasts, which was further attenuated by simvastatin. Conclusion: The lung fibroblasts seem to be the main initially stimulated cells that could potentially trigger the inflammatory response, and be responsible for the eventual onset of chronic lung disease. The involvement of IL-1ß stimulation in systemic inflammatory and proteinase imbalance biomarkers is higher in lung fibroblasts. Apoptosis is not a predominant mechanism in these cells.